PENEGAKAN HUKUM PIDANA TERHADAP PELAKU PENIPUAN YANG DILAKUKAN MELALUI MEDIA ELEKTRONIK BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI TEKNOLOGI ELEKTRONIK OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Megawati, Syarifah; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The sophistication of electronic informatiton technology todai is quite easier for everyone to do a variety of communication with one another. So anything is gettting easier to obtain and acces to information is very easy. Along with the development of information technology is so rapid, certain people can also abuse the means of communication with the electronic media fraud crimes.This type of research can be classified in this type of sociological research. This research was conducted in the city police Pekanbaru, while the sample population is overall the parties relating to the issues examined in this study, the data source used, primary data, secondary data, and the data trertiary, data collection techniques in this study with interviews, questioners, and literature study. Analysis of the data used is qualitative data and techniques by means of deductive inference.From the research there are three main things that can be inferred. First, the occurrence of criminal fraud electronic media is influenced by many factors such as the economic, environmental, social, cultural, easily commit the crime and gullible people power. Second, that there is no law only do prevention is a way appealed through the media. Third, the weakness in law enforcement criminal fraud electronic media it self because of the lack of personnel, facilites and information technology infrastructure that helps the police in the investigation process, in order to uncover th criminal fraud of electronic media. Suggestions Author, First, Police Resor Pekanbaru City must continue to innovate in the face of technological progress and information, this is due to the increase in crime that occure are becoming increasingly sophisticated with ways to improve technology infrastructure in facilitating the investigation. Secondly, a need to improve the quality of human resources of the law enforcement agencies, especially in the handling of criminal fraud through electronic media.Keywords: Law Enforcement - Fraud Electronic Media